Memoria histórica sobre la vida cotidiana en la década de los 50 del siglo XX, en la parroquia Cañi, comunidad Llimbe de la provincia de Chimborazo. - Estrada Gaibor, Kathya Lizbeth (2022)
This research was carried out in the province of Chimborazo, Cañi parish, Llimbe community, with the aim of learning about the historical memory of the daily life of our ancestors in the 50s of the twentieth century, through the collection of data applied to the inhabitants of this community in order to learn about their lifestyles, customs and traditions. The aim of this research was to analyze the living conditions of each of the families of that time, so the research presented a qualitative approach with a descriptive design. At the same time, the techniques used were interviews for data collection. As a result of the research, it was found that the way of life of those people was not the best, there was too much poverty, they didn’t have an adequate education, a community far from society forgotten by the authorities of the country, they did not have basic services, the children in the past had to go out to work consequently they did not study. On the other hand, they did not have adequate roads to be able to move around, adequate roads to be able to move around.